Comparación de las propiedades físicas del biocombustible sólido obtenido a partir de las semillas de Mauritia flexuosa l. Oenocarpus bataua mart y Euterpe oleracea - Ipanama Mendoza, Jhon Patric (2024)
The general objective of this work was to compare the physical properties of solid biofuels obtained from the seeds of Mauritia flexuosa l., Oenocarpus bataua mart and Euterpe oleracea. The research has a comparative descriptive approach. The study population was made up of all the seeds of Mauritia flexuosa l., Oenocarpus bataua mart and Euterpe oleracea from the province of Maynas that are sold in the Belén and Modelo markets. The type of sampling was non-random at the discretion of the authors of this work, it was considered a sample size 3000 g. of Mauritia flexuosa l. seeds, 3000 g. of Oenocarpus bataua mart seeds and 3000 g. of Euterpe oleracea seeds. The results of the average values obtained regarding the biometric properties of the seeds were. for Mauritia flexuosa l., length 49.10 mm, diameter 30.42 mm and weight 27.26 g, Oenocarpus bataua mart, length 28.18 mm, diameter 20.61 mm and weight 9.33 g and Euterpe oleracea, length 11.35 mm, diameter 11.38 mm and weight 2.56 g., and the average results of the mechanical property (resistance) were of Mauritia flexuosa l., 426.33 Kgf, of Oenocarpus bataua mart 95.33 Kgf, of Euterpe oleracea 49 Kgf. The results obtained regarding the average values of the physical and mechanical properties of the solid biofuel obtained were for Mauritia flexuosa l.: density (0.55 g/cm3), Calorific Value (9476.92 Cal/g), Humidity (32.41 %), Flammability ( 34 min.), Compression resistance (104.33 Kgf), Oenocarpus bataua mart: density (0.60 g/cm3), Calorific value (9149.53 Cal/g), Humidity (32.67 %), Flammability (42 min.), Compression resistance (144.67 Kgf), and Euterpe oleracea mart: density (0.61 g/cm3), Calorific Value (8572.99 Cal/g), Humidity (32.08 %), Flammability (39 min.), Compression resistance (113.33 Kgf). When comparing the physical and mechanical properties of the solid biofuel obtained, it is established that the highest calorific value corresponds to Mauritia flexuosa l. and the highest flammability value corresponds to Oenocarpus bataua mart.